DAYA TARIK OBJEK WISATA RELIGI MASJID AGUNG MADANI ISLAMIC CENTER ROKAN HULU - Amilina "; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The background of this research is the phenomenon of the Religi tourist attraction of the Great Mosque of Madani Islamic Center Rokan Hulu specifically related to attractiveness. Specifically this discussion is about what is the pre-eminent attraction in the great Mosque of Madani Islamic Center and the management constraints faced by the great Mosque of Islamic Center. The research method that I use is qualitative, which is a research procedure that produces descriptive data in the form of word sourced from observations, interviews, or secondary data analysis. The author also collects primary data first in the form of document, library data anda other sources. The results of this study are: first, the Great Mosque of Madani Islamic Center which can be seen the unique architecture of the buildings, sights and tourist attractions. Activities that can be carried out at attractions are worship, shopping, climbing tower 99, taking pictures, enjoying Rokan Hulu’s special food and enjoying the facilities available. Great Mosque of Madani Islamic Center provides Madani Mart which sells Muslim fashion and snacks of Rokan Hulu. But there no souvenirs and handicafts that can be made as mementos. The Great Mosque of Madani Islamic Center has an attraction that attracts tourists from the 99 tower because ists height reaches 99 meters and provides a beatiful view because it can attract tourists to visit and climb tower 99. The two obstacles faced by the manager at the Madani Islamic Great Mosque are the funds, because the lack of government attention to the Madani Islamic Center Great Mosque causes development and development constrainsts. Furhermore, human resources because who become officers and work are expected to have the ability and potential and expertise in carrying out work.Keywords: Madani Great Mosque Islamic Center, Attraction, Tower 99